(untitled) (Scientific journal of the Fergana State University, 2024)
The article reveals that the history of the emergence of folk games was formed in connection with economic traditions, relying on sources. In the analysis of the sources, it is said to study the history and development of folk games. Observing the folk games formed over the centuries based on natural conditions and economic traditions during the stages of socio-economic development allows to understand their national identity and their importance in spiritual development. The general and local features of the games, their names, rules are described, a comparative analysis of the processes is carried out.